Hepatitis C Virus Manipulates Humans as its Favorite Host for a Long‐Term Relationship. Issue 2 (29th January 2019) - Ray, Ratna B.; Ray, Ranjit
Abstract : Chronic hepatitis C virus (HCV) infection‐associated liver disease is a global health problem. HCV often causes silent disease, and eventually progresses to end‐stage liver disease. HCV infects hepatocytes; however, initial manifestation of liver disease is mostly displayed in hepatic stellate cells (HSCs), causing fibrosis/cirrhosis, and is believed to occur from inflammation in the liver. It remains unclear why HCV is not spontaneously cleared from infected liver in the majority of individuals and develops chronic infection with progressive liver disease. Direct‐acting antivirals (DAAs) show excellent results in controlling viremia, although beneficial consequence in advanced liver disease remains to be understood. In this review, we highlight the current knowledge that has contributed to our understanding of the role of HCV in inflammation, immune evasion, metabolic disorders, liver pathogeneses, and efforts in vaccine development.